Quality attributes of cinnamon (Cinnamomum verum Bercht & Presl.) accessions grown at Shevroys (Tamil Nadu, India) - Balakrishnamoorthy, R Richard Kennedy, K Nageswari, G (Journal of Spices and Aromatic Crops, 2000)
The quality of bark and leaf of cinnamon (Cinnamomum verum Bercht & Presl.) is determined by their oil and oleoresin contents. The quality of cinnamon is known to vary depending on the region where they are grown (Pruthi 1979). Five accessions of cinnamon collected from Indian Institute of Spices Research, Calicut, are being maintained at Horticultural Research Station, Yercaud (Tamil Nadu, India) (1450 m < MSL). The quality parameters of these accessions were analysed and are reported here.